Futsal Application Products: WEB based Integrated System (FTS) - Saud, Syauqi; Bessy Sitorus Pane; Amir Supriadi (UNIB Press, 2024)
The goal of this project is to create a web-based futsal integrated system (FTS) application. This application will function as a database for clubs affiliated with the North Sumatra district and province futsal associations. The present study employs a research and development process, utilizing nine research steps to build products that aim to address current database system difficulties. Group I test results on 15 trial samples with a total score of 3.90 divided by the maximum score resulted in a presentation of 78.33% with the eligible criteria. Group II trials on 30 Medan City Askot administrators showed that the effectiveness aspect was 93%, the quality aspect was 93.33%, and the product satisfaction aspect was 95% with an average percentage of 93.77% in the